Mycobacterium tuberculosis, a major threat to health in South Africa : intracellular survival after treatment with novel drugs designed against the mycothiol pathway - Mazorodze, James Hove (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Biomedical Sciences))--University of Stellenbosch, 2010.